Study of Deconstruction Characterization of Rahwana in Ramayana Novel by Sunardi DM Related to Character Education and Cultural Value - Hendry Sugara (ppjbsip, 2019)
At present character education is being intensively carried out by the government to restore the cultural character of Indonesia which is considered to be experiencing a crisis. The improvement was carried out through an education curriculum that emphasized the character values in teaching and learning activities. Classical literary work is one of the treasures of Indonesian culture which includes exemplary character values. Epic Ramayana is one of the classical literary works that has exemplary character education values. One of the figures in the Ramayana Epic, namely Rahwana, in the story is the king of the powerful and invincible Kingdom of Alengka. Rahwana has an evil characterization but behind it all, there are things that we can also make as role models. The purpose of this study is to reveal the characterization of Rahwana's character which is then associated with character education and cultural values. This study uses a deconstruction method by conducting an in-depth study of Rahwana figures through texts on the Ramayana novel by Sunardi DM. The results of this study that behind his evil character, Rahwana has six character values, namely religious, hard work, democratic, love of the homeland, caring for the environment, and responsibility. The character value is part of the character education values formulated in the current curriculum. In addition to character values, there are four cultural values contained in Rahwana's figures, namely religious systems, languages, systems of equipment and technology, and the arts system. These cultural values are values that are densely applied in everyday life.